Comparison of Single Axillary vs. Dual Arterial Cannulation for Acute Type a Aortic Dissection: A Propensity Score Matching Analysis - Chang, Yi; Lin, Hongyuan; Qian, Xiangyang; Guo, Hongwei; Yu, Cuntao; Sun, Xiaogang; Wei, Bo; Ma, Qiong; Wei, Yizhen; Shi, Yi (Frontiers in Cardiovascular Medicine, 2022)
Background Optimal arterial cannulation site for acute aortic dissection repair is unclear, especially for complex arch surgery. Axillary artery cannulation is widely accepted but adding a femoral artery cannulation to it was considered to be able to improve perfusion and early outcomes. To clarify this point, a comparison of perioperative outcomes for these two different cannulation strategies was conducted regarding pathological features of dissection. Methods From January 2010 to December 2019, 927 consecutive patients underwent total arch replacement combined with frozen elephant trunk for acute type A aortic dissection. The data including detailed pathological features were retrospectively collected and analyzed. Propensity score matching and multivariate logistic regression analysis were used for adjusting confounders potentially related to outcome. Results 523 patients (56.3%) accepted dual arterial cannulation (DAC group), and 406 patients (43.7%) received single axillary artery cannulation (SAC group). 388 pairs of patients were well-matched. No matter before or after adjusting preoperative characteristics by matching, there were no significant differences on operative mortality (6.7% VS 5.4%, P=0.420 before matching; 5.4% VS 5.4%, P=1.000 after matching), stroke (6.7% VS 5.4%, P=0.420 before matching; 6.4% VS 5.2%, P=0.435 after matching). Spinal cord injury (5.0% VS 5.7%, P=0.640 before matching; 5.4% VS 5.7%, P=1.000 after matching) and acute renal failure requiring dialysis (13.8% VS 9.6%, P =0.050 before matching; 12.6% VS 9.5%, P =0.174) between the two groups. Dual arterial cannulation was not an independent protective factor of operative mortality (odds ratio [OR] 1.01, 95% confidence interval [CI]0.55–1.86), stroke (OR 1.17, 95% CI 0.65–2.11), spinal cord injury (OR 1.17, 95% CI 0.65–2.11) and acute renal failure requiring CRRT (OR 1.24, 95% CI 0.78–1.97) after adjusting for confounding factors by multivariable logistic regression analysis. In subgroup analysis no advantage of dual arterial cannulation was found for particular population. Conclusions Single axillary artery cannulation was competent in complex arch repair for acute aortic dissection, presenting with a satisfactory result as dual arterial cannulation. Adding a femoral artery cannulation was unnecessary unless sufficient flow volume could not be achieved by axillary artery cannulation.